Ultrasound as Diagnostic Tool for Diaphragmatic Myoclonus. Issue 3 (9th January 2016) - Ramos, Vesper Fe Marie Llaneza; Considine, Elaine; Karp, Barbara I.; Lungu, Codrin; Alter, Katharine; Hallett, Mark
Abstract: Background: Diaphragmatic myoclonus is a rare disorder of repetitive diaphragmatic contractions, acknowledged to be a spectrum that includes psychogenic features. Electromyography has been the diagnostic tool most commonly used in the literature. Methods: To test whether we could perform a noninvasive technique to delineate the diaphragm as the source of abnormal movements and demonstrate distractibility and entrainability, we used B‐mode ultrasound in a patient with diaphragmatic myoclonus. Results: Ultrasound imaging clearly delineated the diaphragm as the source of her abdominal movements. We were able to demonstrate entrainability of the diaphragm to hand tapping to a prescribed rhythm set by the examiner. Conclusions: We recommend the use of ultrasound as a noninvasive, convenient diagnostic tool for further studies of diaphragmatic myoclonus. We agree with previous findings that diaphragmatic myoclonus may be a functional movement disorder, as evidenced by distractibility and entrainability demonstrated on real‐time video with ultrasonography.